2022
DOI: 10.22141/2307-1257.11.2.2022.367
|View full text |Cite
|
Sign up to set email alerts
|

Guideline of guidelines: management of recurrent urinary tract infections in women

Abstract: No abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, recent research has revealed potential alternatives such as behavioural modifications, immunoactive prophylactic agents, cranberry, D-mannose, and methenamine hippurate (Hiprex, Inova Pharmaceuticals, Chatswaood, NSW, Australia) amongst others [4]. There currently are no guidelines for the structured management of rUTIs in Australia incorporating appropriately prescribed antibiotics along with these other preventive strategies [7]. We conducted a retrospective cohort study with the aim of assessing how these patients are currently being managed within our department at Eastern Health (Australia), a large tertiary referral centre serving a population of >1 million.…”
mentioning
confidence: 99%
“…In addition, recent research has revealed potential alternatives such as behavioural modifications, immunoactive prophylactic agents, cranberry, D-mannose, and methenamine hippurate (Hiprex, Inova Pharmaceuticals, Chatswaood, NSW, Australia) amongst others [4]. There currently are no guidelines for the structured management of rUTIs in Australia incorporating appropriately prescribed antibiotics along with these other preventive strategies [7]. We conducted a retrospective cohort study with the aim of assessing how these patients are currently being managed within our department at Eastern Health (Australia), a large tertiary referral centre serving a population of >1 million.…”
mentioning
confidence: 99%